Cable Bacteria Activity Modulates Arsenic Release From Sediments in a Seasonally Hypoxic Marine Basin - van de Velde, Sebastiaan J.; Burdorf, Laurine D. W.; Hidalgo-Martinez, Silvia; Leermakers, Martine; Meysman, Filip J. R. (Frontiers in Microbiology, 2022)
Eutrophication and global change are increasing the occurrence of seasonal hypoxia (bottom-water oxygen concentration < 63 µM) in coastal systems worldwide. In extreme cases, the bottom-water can become completely anoxic, allowing sulphide to escape from the sediments and leading to the development of bottom-water euxinia. In seasonally hypoxic coastal basins, electrogenic sulphur oxidation by long, filamentous cable bacteria has been shown to stimulate the formation of an iron oxide layer near the sediment-water interface while the bottom waters are oxygenated. Upon development of bottom-water anoxia, this iron oxide ‘firewall’ prevents the sedimentary release of sulphide. Iron oxides also act as an adsorption trap for elements such as arsenic. Arsenic is a toxic trace metal, and its release from sediments can have a negative impact on marine ecosystems. Yet, it is currently unknown how electrogenic sulphur oxidation impacts arsenic cycling in seasonally hypoxic basins. Here we present results from a seasonal field study of an uncontaminated marine lake, complemented with a long-term sediment core incubation experiment, which reveals that cable bacteria have a strong impact on the arsenic cycle in a seasonally hypoxic system. Electrogenic sulphur oxidation significantly modulates the arsenic fluxes over a seasonal time scale by enriching arsenic in the iron oxide layer near the sediment-water interface in the oxic period, and pulse-releasing arsenic during the anoxic period. Fluxes as large as 20 µmol m-2 d-1 were measured, which are comparable to As fluxes reported from highly contaminated sediments. Since cable bacteria are recognized as active components of the microbial community in seasonally hypoxic systems worldwide, this seasonal amplification of arsenic fluxes is likely a widespread phenomenon.